CDK14 regulates the development and repair of lung - Jian-wei Chen; Yu-xiang Wang; Rong-rong Gao; Lan-yue Ma; Jing Zhong; Jia-xin Yang; Zhao-hua Deng; Yu-yan Li; Xiao-ling Li; Ya-hai Shu; Wen-jing Guo; Zi-yuan Zhou; et al. (Cell Death Discovery)
Abstract Cyclin-dependent kinases (CDK) 14 regulates cell cycle, tumor expansion by influencing the downstream targets of the canonical Wnt signaling pathway. However, the function of CDK14 during organ development and regeneration has not been investigated in genetically-modified animals. Here, we found that genetic ablation of Cdk14 influenced pulmonary vascular endothelial cells and alveolar epithelial cells during mice embryonic development as well as repair of lung after bleomycin or lipopolysaccharide induced injury. Genetic knockout of Cdk14 and the CDK14 covalent inhibitor FMF-04-159-2 resulted in reduction of pulmonary vessel covered area and epithelial cell number, exhibiting increased mortality and more severe lung damage after injury. Mechanistically, Cdk14 ablation inhibited the proliferation of epithelial and vascular endothelial cells, inducing cell cycle arrest at the G2/M phase. Through RNA-seq analysis of both endothelial and epithelial cells, we found that knockdown of Cdk14 controls the expression of signal transducers and activator of transcription 1 (STAT1) as well as associated genes in interferon signaling. Disruption of Cdk14 interferes with IFN-γ induced lung repair in vivo, suggesting potential crosstalk of CDK14 signaling and IFN-γ pathway. Our work highlights the importance of Cdk14 in lung development and regenerative repair through an uncharacterized CDK14- IFN-γ signaling axis.